Experimental testing of pneumatically forced actuated compressor-expander valves. (August 2019) - Stoeckel, C; Thomas, C; Nickl, J; Hesse, U
Abstract: The possibility of forced actuation of valves enables new operation modes for existing reciprocating compressors, e.g. capacity control or reverse operation as expander. A pneumatically forced actuated valve was tested within a reciprocating compressor and a quite complex behaviour was found, as shown in previous publications. A test rig outside of the compressor was set up for a better understanding of the system. Two measurement techniques were used to observe the sealing element motion over the time at varying operating conditions, like applied pressure levels and actuation time. The dependency of the valve motion to those operation conditions is evaluated and discussed. Improvements to the test bench and measurement techniques are also proposed to achieve more accurate results.